1999
DOI: 10.1007/s000110050465
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of M. leprae or M. bovis BCG delipidation on cellular accumulation into mouse pleural cavity. Distinct accomplishment of mycobacterial lipids in vivo

Abstract: Intact M. leprae and its lipids did not incite any cell recruitment. Apolar external cell wall lipids from M. leprae and BCG induce different cellular responses. They seem to have a crucial importance at the first contact of mycobacteria with the host cell, modulating the influx of neutrophils/macrophages in the early (4/24 h) onset of the inflammatory reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This biphasic infiltration was similar to that observed after Mycobacterium bovis BCG (bacillus of Calmette and Guérin) infection, in which the first wave of neutrophils was dependent on activated resident macrophages and the second wave of neutrophils was dependent on activated T cells. [35][36][37] Our previous tumor studies revealed a similar pattern in which tumors cells expressing membrane-only FasL induce an early infiltration of neutrophils, followed later by a more sustained influx of neutrophils that remain present until the tumor is rejected completely. Complete tumor rejection is ultimately dependent on T cells, suggesting T cells may be important in sustaining the influx of neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…This biphasic infiltration was similar to that observed after Mycobacterium bovis BCG (bacillus of Calmette and Guérin) infection, in which the first wave of neutrophils was dependent on activated resident macrophages and the second wave of neutrophils was dependent on activated T cells. [35][36][37] Our previous tumor studies revealed a similar pattern in which tumors cells expressing membrane-only FasL induce an early infiltration of neutrophils, followed later by a more sustained influx of neutrophils that remain present until the tumor is rejected completely. Complete tumor rejection is ultimately dependent on T cells, suggesting T cells may be important in sustaining the influx of neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…as well as differences in receptor use (51), cytokine and chemokine induction may not be comparable (52,53). Previous reports indicate that M. tuberculosis can induce neutrophil, eosinophil, monocyte, and lymphocyte migration (46,48,49,52), as well as chemokine up-regulation in infected monocytes/macrophages (47,49,50). Mycobacterial infections have been shown to activate NF-B via Toll-like receptors, resulting in the enhanced expression of TNF-␣, CCR5, and IL-8 (25, 54 -57).…”
Section: Discussionmentioning
confidence: 99%
“… 24 While the mechanisms linked to biological effects of mycobacterial lipids on host cells are poorly understood, growing evidence highlights their importance in pathogenicity (see Box 1 ). For instance, the delipidation of mycobacterial cells has been associated with both immune activation and suppression 25 ; from gene manipulation experiments, we know that the impairment of biosynthetic lipid pathways may lead to a tremendous decline in virulence of mycobacterial strains 26. , 27.…”
Section: Fat: the Molecular Key Feature In The Tubercle Bacillusmentioning
confidence: 99%